Development and implementation of the AIDA International Registry for patients with Periodic Fever, Aphthous stomatitis, Pharyngitis, and cervical Adenitis syndrome - Della Casa, Francesca; Vitale, Antonio; Cattalini, Marco; La Torre, Francesco; Capozio, Giovanna; Del Giudice, Emanuela; Maggio, Maria Cristina; Conti, Giovanni; Alessio, Maria; Ogunjimi, Benson; Ragab, Gaafar; Emmi, Giacomo; et al. (Frontiers in Pediatrics, 2022)
Objective: Aim of this paper is to illustrate the methodology, design, and development of the AutoInflammatory Disease Alliance (AIDA) International Registry dedicated to patients with the Periodic Fever, Aphthous stomatitis, Pharyngitis, and cervical Adenitis (PFAPA) syndrome. Methods: This is a physician-driven, population- and electronic-based registry proposed to gather real-world demographics, clinical, laboratory, instrumental and socioeconomic data from PFAPA patients. Data recruitment is realized through the on-line Research Electronic Data Capture (REDCap) tool. This registry is thought to collect standardized information for clinical research leading to solid real-life evidence. The international scope and the flexibility of the registry will facilitate the realization of cutting-edge study projects through the constant updating of variables and the possible merging and transfer of data between current and future PFAPA registries. Results: 112 centers have already been involved from 23 countries and 4 continents starting from August 24th, 2021, to April 6th, 2022. 56/112 have already obtained the formal approval from their local Ethics Committees. The platform counts 321 users (113 principal investigators, 203 site investigators, two lead investigators, and three data managers). The registry collects retrospective and prospective data using 3856 fields organized into 25 instruments, including PFAPA patient’s demographics, medical histories, symptoms, triggers/risk factors, therapies, and impact on the healthcare systems. Conclusions: The development of the AIDA International Registry for PFAPA patients will enable the on-line collection of standardized data prompting real-life studies through the connection of worldwide groups of physicians and researchers. This project can be found on https://clinicaltrials.gov NCT 05200715.